2008
DOI: 10.1152/ajpregu.00884.2007
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent hypoxia reduces ventilatory long-term facilitation and enhances apnea frequency in newborn rats

Abstract: Ventilatory long-term facilitation (LTF; defined as gradual increase of minute ventilation following repeated hypoxic exposures) is well described in adult mammals and is hypothesized to be a protective mechanism against apnea. In newborns, LTF is absent during the first postnatal days, but its precise developmental pattern is unknown. Accordingly, this study describes this pattern of postnatal development. Additionally, we tested the hypothesis that chronic intermittent hypoxia (CIH) from birth alters this de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 53 publications
5
73
2
Order By: Relevance
“…Although we have previously shown that this pattern of n-IH exposure enhances the ventilatory response to repeated hypoxic cycles (i.e., involving peripheral chemoreceptors) in 10-day-old rats (25), our actual results show that this altered response is not persistent in adults. Contrastingly, responses involving central integration of the cardiorespiratory control system (posthypoxic frequency decline and phrenic LTF) are altered in adult rats exposed to n-IH.…”
Section: Perspectives and Significancecontrasting
confidence: 78%
See 4 more Smart Citations
“…Although we have previously shown that this pattern of n-IH exposure enhances the ventilatory response to repeated hypoxic cycles (i.e., involving peripheral chemoreceptors) in 10-day-old rats (25), our actual results show that this altered response is not persistent in adults. Contrastingly, responses involving central integration of the cardiorespiratory control system (posthypoxic frequency decline and phrenic LTF) are altered in adult rats exposed to n-IH.…”
Section: Perspectives and Significancecontrasting
confidence: 78%
“…We have recently reported in rat pups that n-IH during 10 days from birth increases ventilatory response to brief (50 s) hypoxic exposure (25), strongly suggesting higher sensitivity of peripheral chemoreceptors as reported by in vitro recordings (47), while the ventilatory LTF was suppressed (25), as reported by Reeves et al (50) in 2-mo-old rats raised under n-IH for 30 days from birth. Accordingly, this model might be useful to determine whether n-IH-related alterations in respiratory regulation persist into adulthood and alter the central integration of peripheral chemoreceptor inputs.…”
supporting
confidence: 66%
See 3 more Smart Citations